The Enquiridion, i.e. the Philosophy of Christ - Santos López, Modesto (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Erasmus's Enquiridion immerses itself in the religious spirit of Medieval Europe. Erasmus's educational background, with a finely humanistic nuance, is a constant feature in his works. El Manual del Caballero Cristiano, outlined at the request of a lady who asked Erasmus for help to prevent her husband from leading a lustful life, turns out to be a manual or a breviary in which the ideal of the true Christian gentleman is synthesized. Written as a manual of strategies, through twenty-two rules, the author will prepare the Christian gentleman to achieve the victory in the battle between flesh and spirit. By taking the prayer and The Holy Bible as a starting point, Erasmus will wage a battle against the enemies who, since the Original Sin, have been awaiting for mankind. Erasmus presents the religious experiences in the society of his time. And although he proves himself to be critic, not always does he handle the facts in a cautious way. Mainly those facts dealing with the external aspects that have arisen out of religious practices.
Keywords: Enquiridion; Christian gentleman; popular religious feeling; prayer; Holy Bible; flesh-spirit; external-internal.